Faktor-Faktor yang Mempengaruhi Perilaku Hand Hygiene Perawat di Puskesmas Telaga - Sabirin B.Syukur; Fadli Syamsuddin; Desriyanti Djumuli (Pusat Riset dan Inovasi Nasional, 2023)
Some factors that affect hand hygiene behavior are internal factors and external factors. The purpose of this study is to determine the relationship between hand hygiene behavior and internal factors such as attitudes and knowledge while external factors such as facility availability. The design of this study uses quantitative methods, namely research related to data and figures. Data analysis using chi-square. Sampling using total sampling. The results of the study found that the relationship between attitudes and good behavior (70.0%) and less attitudes (77.8%), The relationship between knowledge and behavior obtained was high (33.3%) and moderate (40.0%) while the relationship between facility availability was obtained which was good (56.3%) and less (43.8%). The results of the statistical analysis obtained the relationship between attitudes and hand hygiene behavior p = 0.037, the relationship between knowledge and hand hygiene behavior p = 0.245 and the relationship between the availability of facilities with hand hygiene p = 0.073, it can be concluded that there is a significant relationship between hand hygiene behavior and attitudes, knowledge and availability of facilities.